IMPLEMENTASI PROSES PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN BAGI PENGEMBANGAN SEMANGAT BELA NEGARA MAHASISWA - Deny Surya Permana (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2018)
This study is back grounded by author’s anxiety toward the fading of state defence spirit of citizen included college students. This study use qualitative approach with descriptive method. Data of study is obtained by interview, observation, and documentation study. Result of study reveal that: 1) Lecturer team of Civic Education, MKDU Department develop Syllabus by concerning student’s cognitive, affective and psychomotor domain, then this Syllabus is used to become reference to develop Lecturing Program Unit by civic education lecturers; 2) Syllabus and Lecturing Program Unit that have been designed in implementation in class undergo much adjustments; 3) The development of student’s state defence spirit is done in learning process by discussing more deeply Indonesia geo politic and geo strategy topics because state defence topic is integrated in those two subject matter. Whereas strategy that is implemented by lecturer is by giving example of state defence behaviour and through the story of nation struggle history that contain nationalism and patriotism value; 4) State defence spirit is done by college student by learning persistently to actualize knowledge potency, active in university student affair organization, have achievement, fortify him/herself from negative foreign culture, and apply Indonesian-ness values in attitude and behaved. Thus, college student’s predicate as agent of change, social control, and iron stock can be actualized, because self devote according to his/her profession and predicate as a college students for the sake of nation and state interest included in state defence.